Is the UWWTD Implementation Delivering Results for the People, the Economy, and the Environment of the Danube Region? : A Wastewater Management Assessment Based on the World Bank's Engagement - World Bank (World Bank, Washington, DC, 2018)
This review of wastewater management in Danube region under EU water policies shows that, despite several challenges, the UWWTD has indeed delivered results for the people and environment in Danube region. The share of wastewater treated according to the UWWTD requirements is showing a major improvement since 2004, demonstrating impact of massive investment efforts undertaken, and resulting in significant emission reduction in the recent past. This has resulted in a noticeable water quality improvement over the last 20 years for both organic pollutants and nutrients. At the same time, the review points out to several challenges. Implementation capacity is often neglected and insufficiently prepared. The necessary tariff increases, a consequence of investment in new infrastructure and related O&M cost increases, trigger affordability issues for the bottom 40 percent of population. A lack of the necessary sectoral institutional reforms, has resulted in lower than planned absorption of available funds and delays in UWWTD compliance. These challenges also represent opportunities in the implementation of the current Directive within and beyond the Member States, and its potential review. The current implementation of the Directive could be made more efficient using sound economic appraisal to prioritize investments according to their cost-effectiveness while maintaining public health and environmental benefits and achievement of WFD objectives.